A randomized comparative study of patient-controlled epidural analgesia with manual standard intermittent bolus for labor analgesia - Manish Banjare,; Aditi Kaushal,; Deepali Valecha ,; Nandini Bhatt,; K. K. Arora, (Asian Journal of Medical Sciences, 2023)
Background: Patient-controlled epidural analgesia (PCEA) pump has proven to reduce the incidence of unscheduled clinician interventions and total dose of local anesthetic administered for labor pain. Aims and Objectives: The aim of the study was to compare the quality of analgesia, maternal satisfaction, amount of rescue analgesia needed, and neonatal outcome between clinician delivered manual bolus doses and PCEA pumps for epidural labor analgesia. Materials and Methods: 60 parturients of the American Society of Anesthesiologists II scheduled for normal vaginal delivery were randomly divided into two groups, Group A (PCEA) and Group B (Manual bolus). Both groups received an initial epidural bolus of 10 mL of 0.125% Inj. Bupivacaine+20 mcg injection fentanyl. Group A (PCEA) patients received a basal infusion of 5 mL/h with self-administered bolus of 2 mL with a lockout interval of 15 min. Group B patients were provided with a bolus of 10 mL of the same solution manually after every hour. Patients of both groups were given manual rescue boluses for distressing pain (visual analog scale [VAS] >5). Results: Mean VAS score in Group A was 2.97±0.73; and in Group B, it was 3.03±0.56 (P>0.05). Total bupivacaine use and mean duration of second stage of labor in both groups was found comparable. Mean top-up requirement of local anesthetics was significantly high in Group B. Maternal satisfaction was also higher in PCEA group. Conclusion: As PCEA pump provides continuous infusion of local anesthetics, there was lesser requirement of top ups of bupivacaine and higher maternal satisfaction score in PCEA group than manual bolus group.